Preparation method of catalyst slurry of medium-high temperature fuel cell based on polybenzimidazole

By adding polybenzimidazole (PBI) to the catalyst slurry, the preparation process is optimized, and the problem of phosphoric acid loss in high-temperature proton exchange membrane fuel cells is solved, and the proton conduction efficiency and battery performance are improved.

CN120261593APending Publication Date: 2025-07-04SHANDONG ZHENGENTROPY ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510406831.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In existing high-temperature proton exchange membrane fuel cells, severe phosphoric acid loss leads to hindered proton transmission and increased mass transfer impedance, which affects battery performance and stability.

Method used

Add nitrogen group polymer polybenzimidazole (PBI) to the catalyst slurry to optimize the composition and content of the binder. The catalyst slurry is prepared by magnetic stirring, water bath ultrasonication, ball milling and other methods to regulate the solid content and proportion.

Benefits of technology

It effectively improves the loss of phosphoric acid in the catalytic layer, optimizes the proton conduction efficiency, reduces mass transfer polarization, and improves the overall performance of medium and high-temperature fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261593A_ABST
    Figure CN120261593A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of catalyst slurry of a medium-high temperature fuel cell based on polybenzimidazole, and belongs to the field of medium-high temperature proton exchange membrane fuel cells. The PBI is added, so that the problem of loss of phosphoric acid in the catalyst layer during operation of the battery is effectively improved, the proton conduction efficiency is optimized, the performance of the membrane electrode is improved, especially under high current density, the mass transfer polarization is reduced, and the overall performance of the battery is remarkably improved. Besides, the preparation method is simple and convenient to operate, the process is easy to control, the prepared catalyst slurry is suitable for various electrode preparation processes by regulating and controlling the solid content, and a new effective way is provided for development of a medium-high temperature fuel cell technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medium and high temperature proton exchange membrane fuel cells, and particularly relates to a method for preparing catalyst slurry. Background Art

[0002] As a highly potential new generation power generation technology, proton exchange membrane fuel cells (PEMFCs) have shown broad application prospects in many fields such as automobiles, stationary power plants, and aerospace due to their significant advantages such as high efficiency, low noise, and zero emissions. Among them, high temperature proton exchange membrane fuel cells (HT-PEMFC) operate at a temperature of 120 - 200 °C. Compared with traditional low temperature proton exchange membrane fuel cells (LT-PEMFC), they have stronger impurity tolerance and a simpler water and heat management system, and thus have a wider application prospect. However, when preparing high temperature proton exchange membrane fuel cells (HT-PEMFC), common binders mainly include fluoropolymers such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF). Although these hydrophobic fluoropolymers can improve the hydrophobicity of the catalyst layer to a certain extent, reduce the phenomenon of "acid flooding" of phosphoric acid, and increase the contact opportunity between reaction gases and Pt catalysts, with the increase of water vapor emission during the operation of the battery, the loss of phosphoric acid in the catalyst layer is aggravated, proton transport is blocked, and mass transfer impedance increases, seriously affecting the discharge performance of HT-PEMFC. To sum up, there are obvious deficiencies in the prior art in solving phosphoric acid loss and optimizing proton conduction, and an innovative solution is urgently needed to improve the performance and stability of HT-PEMFC. Summary of the Invention

[0003] In view of the above situation, to overcome the defects of the prior art, the present invention provides an innovative method for preparing a catalyst slurry for medium and high temperature fuel cells based on polybenzimidazole.

[0004] To achieve the above object, the following technical solutions are adopted: The present invention starts from regulating the composition of the catalyst layer, by optimizing the composition and content of the binder, adding an appropriate amount of nitrogen group polymer (such as polybenzimidazole, PBI) to the catalyst slurry system with a fluoropolymer as the binder, and precisely regulating the ratio between the two, including the following steps:

[0005] S1. First, a high-temperature resistant alloy catalyst (such as at least one of carbon-supported platinum-based catalysts such as PtCo / C, PtNi / C, PtFe / C, and Pt / C supported on a graphitized carrier, with a Pt mass fraction of 10% - 60%) is wetted and mixed with an appropriate amount of deionized water;

[0006] S2. A fluoropolymer (such as at least one of polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF, perfluoroethylene-propylene copolymer FEP, and ethylene-tetrafluoroethylene copolymer ETFE) is mixed with water and dispersed to obtain a hydrophobic agent solution;

[0007] S3. Disperse the nitrogen-containing polymer PBI in an alcohol (at least one of small molecule alcohols such as ethanol, ethylene glycol, n-propanol, isopropanol, propylene glycol, etc.) to obtain an ionomer solution;

[0008] S4. Dropwise add the hydrophobic agent solution and the ionomer solution to the catalyst in sequence, and after dispersion, obtain a catalyst slurry with a solid content of 1%-15%, a volume ratio of water to alcohol of 1:(0.5-4), and a mass percentage of nitrogen-containing polymer to fluorine-containing polymer of 1-20%. The dispersion method can be selected from at least one of magnetic stirring, water bath ultrasonic, homogeneous dispersion, and ball milling dispersion.

[0009] Furthermore, wet the Pt / C catalyst in the step S1 with an appropriate amount of deionized water and mix it thoroughly. Deionized water can effectively avoid the influence of impurities on the performance of the catalyst;

[0010] Furthermore, after ultrasonic dispersion in an ice bath (power 700W, time 30min, temperature 3°C) in the step S2, perform magnetic stirring dispersion (rotation speed 650r / min, time 30min, 40min, 45min);

[0011] Furthermore, react for 1h under the condition of magnetic stirring at 80°C and 800r / min in the step S3;

[0012] Furthermore, set the dropping rate to 1ml / s in the step S4;

[0013] Furthermore, in the dispersion in the step S4, first use ultrasonic dispersion at a rate of 700W for 30min; then perform homogeneous dispersion, set the rotation speed to 12000r / min, and the time to 2h; finally, perform ball milling treatment using a planetary ball mill, set the rotation speed to 500r / min, and the time to 48h. After ball milling, perform sieving to remove unevenly dispersed particles to obtain a catalyst slurry that meets the requirements.

[0014] The beneficial effects of the present invention are as follows: Compared with the prior art, the present invention has achieved remarkable technical effects. By adding PBI, the loss problem of phosphoric acid in the catalytic layer during battery operation is effectively improved, the proton conduction efficiency is optimized, and the performance of the membrane electrode is enhanced. Especially at high current density, the mass transfer polarization is reduced, and the overall performance of the battery is significantly improved. In addition, the preparation method of the present invention is simple to operate and the process is easy to control. The prepared catalyst slurry is suitable for various electrode preparation processes by adjusting the solid content, providing a new effective way for the development of medium and high temperature fuel cell technology. Description of the Drawings

[0015] Figure 1 It is the electrode voltage-current density curve of Example 1 and Comparative Example 1 of the present invention;

[0016] Figure 2 This is the electrode voltage-current density curve of Example 2 and Comparative Example 2 of the present invention;

[0017] Figure 3 This is the electrode voltage-current density curve of Example 3 and Comparative Example 3 of the present invention;

[0018] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation to the present invention. Detailed implementation manners

[0019] The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0020] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to the described content can be applied to the present invention. The preferred implementation methods and materials described herein are only for illustrative purposes and do not limit the content of this application.

[0021] The experimental methods in the following embodiments are all conventional methods unless otherwise specified. The test materials used in the following embodiments are all obtained from commercial channels unless otherwise specified.

[0022] Example 1

[0023] A method for preparing a catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole, comprising the following steps:

[0024] S1. Mixing the catalyst and water: Take 5 g of Pt / C catalyst with a mass fraction of 30%, add 10 g of deionized water, and stir well to completely wet the catalyst, ensuring that the catalyst particles are evenly dispersed in the water.

[0025] S2. Preparing the hydrophobic agent solution: Measure 1.8 g of PTFE emulsion, add 60 g of deionized water, first perform ice bath ultrasonic dispersion with an ultrasonic power set to 700 W for 30 min, control the temperature at 3°C to preliminarily disperse the PTFE; then perform magnetic stirring dispersion at a rotation speed of 650 r / min for 30 min to obtain a uniform and stable PTFE solution.

[0026] S3. Preparation of ionomer solution: Weigh 0.55 g of PBI powder, add 150 ml of isopropanol, stir on a magnetic stirrer, set the temperature at 80 °C and the rotation speed at 800 r / min, and stir for 1 h to fully dissolve PBI in isopropanol to form a homogeneous ionomer solution.

[0027] S4. Preparation of catalyst slurry: Drop the PTFE solution and the PBI ionomer solution onto the catalyst at a speed of 1 ml / s in sequence. After dropping, perform ultrasonic dispersion (power 700 W, time 30 min), homogenization dispersion (rotation speed 12,000 r / min, time 2 h), and ball milling dispersion (rotation speed 500 r / min, time 48 h) in sequence, and finally obtain the catalyst slurry by sieving.

[0028] Example 2

[0029] A method for preparing a catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole, comprising the following steps:

[0030] S1. Mix the catalyst and water: Similar to Example 1, add 10 g of deionized water to 5 g of 30% Pt / C catalyst to fully wet the catalyst.

[0031] S2. Preparation of hydrophobic agent solution: Mix 1.5 g of PVDF emulsion with 60 g of deionized water, first perform ice bath ultrasonic dispersion with a power of 700 W and a time of 30 min, and control the temperature at 3 °C; then perform magnetic stirring dispersion with a rotation speed of 650 r / min and stir for 45 min to obtain the PVDF solution.

[0032] S3. Preparation of ionomer solution: Similar to Example 1, weigh 0.55 g of PBI powder, add 150 ml of isopropanol, stir on a magnetic stirrer, set the temperature at 80 °C and the rotation speed at 800 r / min, and stir for 1 h to fully dissolve PBI in isopropanol to form a homogeneous ionomer solution.

[0033] S4. Preparation of catalyst slurry: Drop the PVDF solution and the PBI ionomer solution onto the catalyst at a speed of 1 ml / s in sequence. After dropping, perform ultrasonic dispersion (power 700 W, time 30 min), homogenization dispersion (rotation speed 12,000 r / min, time 2 h), and ball milling dispersion (rotation speed 500 r / min, time 48 h) in sequence, and finally obtain the catalyst slurry by sieving.

[0034] Example 3

[0035] A method for preparing a catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole, comprising the following steps

[0036] S1. Mix the catalyst and water: Similar to Example 1, add 10 g of deionized water to 5 g of 30% Pt / C catalyst and fully wet the catalyst.

[0037] S2. Prepare the hydrophobic agent solution: Take 2 g of FEP emulsion and mix it with 60 g of deionized water. After ultrasonic dispersion in an ice bath (power 700 W, time 30 min, temperature 3 °C), perform magnetic stirring dispersion (rotation speed 650 r / min, time 40 min) to obtain the FEP solution.

[0038] S3. Prepare the ionomer solution: Similar to Example 1, weigh 0.55 g of PBI powder, add 150 ml of isopropanol, stir on a magnetic stirrer, set the temperature to 80 °C, rotation speed 800 r / min, and stir for 1 h to fully dissolve PBI in isopropanol to form a homogeneous ionomer solution.

[0039] S4. Prepare the catalyst slurry: Drop the FEP solution and the PBI ionomer solution into the catalyst at a speed of 1 ml / s in sequence. After dropping, perform ultrasonic dispersion (power 700 W, time 30 min), homogenization dispersion (rotation speed 12000 r / min, time 2 h), and ball milling dispersion (rotation speed 500 r / min, time 48 h) in sequence, and finally pass through a sieve to obtain the catalyst slurry.

[0040] Comparative Example 1

[0041] The difference from Example 1 is that during the preparation of the catalyst slurry, the nitrogen group polymer PBI is not added, the solvent of the PTFE solution uses a water-alcohol mixture with the same ratio as in Example 1, and the catalyst slurry only contains 30% Pt / C catalyst, water, isopropanol, and PTFE. Other steps are the same as S1, S2, and S4 in Example 1.

[0042] Comparative Example 2

[0043] The difference from Example 2 is that during the preparation of the catalyst slurry, the nitrogen group polymer PBI is not added, the solvent of the PVDF solution uses a water-alcohol mixture with the same ratio as in Example 2, and the catalyst slurry only contains 30% Pt / C catalyst, water, ethanol, and PTFE. Other steps are the same as S1, S2, and S4 in Example 2.

[0044] Comparative Example 3

[0045] The difference from Example 3 is that during the preparation of the catalyst slurry, the nitrogen group polymer PBI is not added, the solvent of the PVDF solution uses a water-alcohol mixture with the same ratio as in Example 3, and the catalyst slurry only contains 30% Pt / C catalyst, water, ethanol, and PTFE. Other steps are the same as S1, S2, and S4 in Example 3.

[0046] Result Analysis

[0047] The catalyst slurries obtained from Examples 1 - 3 and Comparative Examples 1 - 3 were respectively made into membrane electrodes with a size of 25 cm 2 , and their power generation performance was detected by polarization curves. Referring to Figures 1 - 3 , it can be clearly seen from the measured polarization characteristic curves of the polybenzimidazole high-temperature membrane electrodes that the membrane electrodes prepared in Examples 1 - 3 have smaller polarization losses. Especially at high current densities, the mass transfer polarization is significantly reduced, resulting in a substantial improvement in the overall performance of the battery. This fully demonstrates that by adding PBI and optimizing the preparation process, the present invention can effectively improve the performance of the catalyst slurry, and thus enhance the performance of medium- and high-temperature fuel cells.

[0048] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

[0049] The above describes the present invention and its embodiments. Such description is not restrictive. What is shown in the drawings is only one of the embodiments of the present invention, and the actual application is not limited thereto. Generally speaking, if those of ordinary skill in the art are inspired by it and design similar methods and embodiments without creative efforts without departing from the purpose of the present invention, they should fall within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole, characterized in that: Including the following steps S1. First, wet and mix a high-temperature resistant alloy catalyst with an appropriate amount of deionized water to prepare a catalyst; S2. Mix and disperse a fluoropolymer with water to obtain a water repellent solution; S3. Disperse a nitrogen-containing polymer PBI in an alcohol to obtain an ionomer solution; S4. Dropwise add the water repellent solution and the ionomer solution to the catalyst in sequence, and after dispersion, obtain a catalyst slurry with a solid content of 1%-15%, a volume ratio of water to alcohol of 1:(0.5-4), and a mass percentage of nitrogen-containing polymer to fluoropolymer of 1-20%. The dispersion method can be selected from at least one of magnetic stirring, water bath ultrasound, homogenization dispersion, and ball milling dispersion.

2. The preparation method of the catalyst slurry for the medium and high temperature fuel cell based on polybenzimidazole according to claim 1, characterized in that: In step S1, the alloy catalyst includes at least one of carbon-supported platinum-based catalysts such as PtCo / C, PtNi / C, PtFe / C, and Pt / C supported on a graphitized carrier, and the mass fraction of Pt is 10%-60%.

3. The preparation method of the catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole according to claim 1, wherein: In step S2, the fluoropolymer includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene-propylene copolymer (FEP), and ethylene-tetrafluoroethylene copolymer (ETFE), and a water repellent solution with a mass fraction of 10%-60%.

4. The preparation method of the catalyst slurry for the medium and high temperature fuel cell based on polybenzimidazole according to claim 1, wherein: In step S3, the alcohol includes at least one of small molecule alcohols such as ethanol, ethylene glycol, n-propanol, isopropanol, and propylene glycol obtained by this method, and the mass fraction is 5%-50%.

5. The preparation method of the catalyst slurry for the medium and high temperature fuel cell based on polybenzimidazole according to claim 1, characterized in that: The catalyst slurry obtained after dispersion has a solid content controlled at 1%-15% and a volume ratio of water to alcohol of 1:(0.5-4).

6. The preparation method of the catalyst slurry for the medium and high temperature fuel cell based on polybenzimidazole according to claim 3, wherein: In step S2, when magnetic stirring for dispersion, the rotation speed is controlled at 500-1000 r / min, and the stirring time is 10-60 min; when ice bath ultrasound is used, the ultrasound power is set at 50-700 W, the ultrasound time is 0.5-3 h, and the temperature is maintained at 0-10 °C.

7. The preparation method of the catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole according to claim 4, wherein: In step S3, when magnetic stirring, the rotation speed is 500-1000 r / min, the temperature is controlled at 50-150 °C, and the stirring time is 10-60 min; when water bath ultrasound is used, the ultrasound power is 50-700 W, and the ultrasound time is 0.5-3 h.

8. The preparation method of the catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole according to claim 1, characterized in that: In step S4, when the water repellent solution and the ionomer solution are dropwise added to the catalyst in sequence, the dropping speed is controlled at 0.5-5 ml / s.

9. The preparation method of the catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole according to claim 8, characterized in that: In step S4, the magnetic stirring rotation speed is 500-1000 r / min, and the time is 1-6 h; the ice bath ultrasound power is 50-700 W, the ultrasound time is 0.5-3 h, the temperature is 0-10 °C, the homogenization dispersion rotation speed is 5000-15000 r / min, and the time is 0.5-3 h; for ball milling dispersion, a planetary ball mill is used, the rotation speed is 350-550 r / min, and the working time is 5-50 h.

10. A catalyst slurry for a medium and high temperature fuel cell based on polybenzimidazole, characterized in that: The catalyst slurry of the medium and high temperature fuel cell of the polybenzimidazole is prepared according to any one of claims 1-9.